Restoration of the anti-proliferative and anti-migratory effects of 1, 25-dihydroxyvitamin D by silibinin in vitamin D-resistant colon cancer cells. Issue 2 (1st July 2015) - Bhatia, Vandanajay; Falzon, Miriam
Highlights HT-29 cells were used as a model system for the intestinal epithelial. TNF-α increased Snail1 and Slug levels, and decreased vitamin D receptor levels. The TNF-α effects were reversed by the flavonolignan silibinin. HT-29 cells are resistant to 1, 25D's anti-proliferative and anti-migratory effects. Co-treatment with silibinin rendered HT-29 cells responsive to 1, 25D.